2020
DOI: 10.3389/fpls.2020.00954
|View full text |Cite
|
Sign up to set email alerts
|

In Support of Winge's Theory of “Hybridization Followed by Chromosome Doubling”

Abstract: Polyploidy-or chromosome doubling-plays a significant role in plant speciation and evolution. Much of the existing evidence indicates that fusion of unreduced (or 2n) gametes is the major pathway responsible for polyploid formation. In the early 1900s, a theory was put forward that the mechanism of "hybridization followed by chromosome doubling" would enable the survival and development of the hybrid zygote by providing each chromosome with a homolog with which to pair. However, to date there is only scant emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…For example, they may simply have come from a cross between a tetraploid (of whatever type) and a hexaploid, or even from the union of an unreduced 2 x gamete from R. nathaliae and a 3 x gamete from a hexaploid. These pentaploid individuals could also play a role as mediators of gene flow, but without forming an independent evolutionary unit ( Tel-Zur et al, 2020 ; Peskoller et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, they may simply have come from a cross between a tetraploid (of whatever type) and a hexaploid, or even from the union of an unreduced 2 x gamete from R. nathaliae and a 3 x gamete from a hexaploid. These pentaploid individuals could also play a role as mediators of gene flow, but without forming an independent evolutionary unit ( Tel-Zur et al, 2020 ; Peskoller et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work indicating the presence of unreduced gametes in H. megalanthus [ 22 ] suggested that the pentaploid hybrids probably originated from a fertilization event between an unreduced (4 n ) egg cell [ 22 , 34 ] from H. megalanthus and a normal haploid ( n ) pollen grain from the diploid paternal species [ 22 ]. The origin of the hexaploid hybrids was further studied using hybrids from an embryo rescue procedure following the crossing of H. megalanthus with H. undatus [ 35 ]. The findings indicated that these hexaploid hybrids were a result of hybridization followed by chromosome doubling at the very early stages of embryo development; see below the section, Embryo rescue following homoploid and interploid interspecific crosses.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting putative hybrids showed triploid, tetraploid and higher ploidy levels, and fAFLP proved their hybrid origin [ 64 ]. Fruit morphology of the true hybrids combined the traits of the two parents, but fruit weight was statistically significantly lower than that of the parents, with the hexaploid hybrids bearing smaller fruit than the pentaploid hybrids [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations